2016
DOI: 10.5897/err2016.2688
|View full text |Cite
|
Sign up to set email alerts
|

A study on the role of computers in adult education

Abstract: This paper discusses how knowledge of computers can affect our daily personal life as well as in the workplace in Greece. Our research is concerned with how useful the knowledge of computers is in the everyday life and work of adults and attempts to investigate the interest of adults for learning computer programmes and different subjects via computers. The research took place from March 30 to April 10, 2015, in Lamia, Greece. Fifty individual adults aged 18-65 years old participated in this study. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, when the number of reference projections is large, the correction efficiency may be reduced. The current common approaches are to use image alignment methods (e.g., ECC [24], single-step DFT algorithm [25], SURF [26], and variants of SURF [27,28]) to accelerate the correction.…”
Section: Drift Artifacts Correction Methods Based On Reference Projec...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the number of reference projections is large, the correction efficiency may be reduced. The current common approaches are to use image alignment methods (e.g., ECC [24], single-step DFT algorithm [25], SURF [26], and variants of SURF [27,28]) to accelerate the correction.…”
Section: Drift Artifacts Correction Methods Based On Reference Projec...mentioning
confidence: 99%
“…The proposed method is compared with the mainstream methods for nanoCT drift artifacts correction, which are reference-projections-based methods. ECC [24] and single-step DFT algorithm [25] use projection intensity to align projections. LPM [27] and RANSAC [28] are variants of SURF that eliminate outliers from the original features (extracted by SURF) to achieve accurate projection alignment.…”
Section: Experiments Settingmentioning
confidence: 99%
“…If the number of data points in the ith dimension in the data space is N , the mean square deviation is S, the mean value is Xi , and the attribute accuracy is δ i , the attribute accuracy calculation method is as follows [5]:…”
Section: Extraction and Filtering Of Association Rulesmentioning
confidence: 99%
“…10 Other reports also support our study outcomes. [11][12][13] In contrast to this statement, a Cochrane database in 2013 concluded that no amniotomy should be done routinely. The review included 15 studies on 5583 women.…”
Section: Effect On Neonatal Outcomementioning
confidence: 99%